2014
DOI: 10.1111/aas.12356
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine provides neuroprotection: impact on ketamine‐induced neuroapoptosis in the developing rat brain

Abstract: In conclusion, ketamine caused neuroapoptosis and impaired brain functions in the developing rat brain which can be effectively attenuated by dexmedetomidine. Dexmedetomidine alone was not neurotoxic to the developing brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 19 publications
3
73
0
1
Order By: Relevance
“…In addition to studies of neonatal anesthetic exposure, a number of studies of fetal anesthetic exposure in rodents, sheep, and non-human primates have been published; neuroapoptosis and other neurodegenerative changes are described with fetal exposure to ketamine, propofol, volatile anesthetic agents, barbiturates, and benzodiazepines [19][20][21][22] .…”
Section: Anesthetic Neurotoxicity In Animal Models Of the Developing mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to studies of neonatal anesthetic exposure, a number of studies of fetal anesthetic exposure in rodents, sheep, and non-human primates have been published; neuroapoptosis and other neurodegenerative changes are described with fetal exposure to ketamine, propofol, volatile anesthetic agents, barbiturates, and benzodiazepines [19][20][21][22] .…”
Section: Anesthetic Neurotoxicity In Animal Models Of the Developing mentioning
confidence: 99%
“…Since the Sanders paper in 2009, there have been 9 additional published studies in fetal or neonatal animal models assessing dexmedetomidine's effect on neuroapoptosis. Of these 10 total studies, 8 demonstrate no neuroapoptosis, and in all 3 studies that conducted later neurobehavioral testing in surviving animals, dexmedetomidine ameliorated the deficits associated with isoflurane administration [19][20][21][22][36][37][38][39][40] ( Table 2 ). In a study by Pancaro et al [40] , dexmedetomidine at very high doses did result in neuroapoptosis in the sensory cortex and the thalamus.…”
Section: Effect Of Anesthesia On the Developing Brainmentioning
confidence: 99%
“…In recent years, increasing basic and clinical studies have proved that DEX protected against different types of organs. Duan et al (10) reported that DEX was not neurotoxic and attenuated neuroapoptosis; other studies indicated that DEX application following cardiac surgery was associated with a lower incidence of atrial arrhythmias (11); Dexmedetomidine protects against acute kidney injury through downregulating inflammatory reactions in endotoxemia rats (12,13). However, mechanisms of the DEX protective effects are unclear, particularly for renal protection.…”
Section: Introductionmentioning
confidence: 99%
“…Since the antagonist atipamezole of the α2-adrenoceptor only partly reversed the neuroprotective effects of dexmedetomidine on neurotoxicity in rats induced by isoflurane, there may be other mechanisms. Several pathways have been reportedly involved in the neuroprotection of dexmedetomidine (Cai et al, 2014;Duan et al, 2014;Liao et al, 2014;Xiong et al, 2014). Li et al (2014) found that dexmedetomidine pretreatment dose-dependently inhibited isofluraneinduced neuroapoptosis by preserving the PI3K/Akt pathway in the hippocampus in neonatal rats.…”
Section: Discussionmentioning
confidence: 99%